Corrosion evaluation on mild steel in different selected media - Silas Oseme Okuma; Orhorhoro Ejiroghene Kelly; Tamuno R.I (International Journal of Engineering Applied Sciences and Technology, 2020)
Mild steel is a key materials used for construction work in the industry but its susceptibility to corrosion in humid air, acidic and other environments are the major obstacles that limit its usage in large scale. In this research work, an assessment of corrosion of locally produced mild steel in tetraoxosulphate (VI) acid (H2SO4), hydrochloric acid (HCl), underground soil and fresh water has been considered. The collected samples from Aladja,Warri, Delta State, Nigeria after chemical analysis were machined to the same sizes. Each of the samples was immersed in equal volumes of the selected media. The assessment of effect of corrosion on the mild steel samples used was carried out via weight loss at various exposure times which lasted for duration of 45 days. The results obtained indicated that tetraoxosulphate (VI) acid was most aggressive environment while fresh water the least. The average weight losses obtained are 5.02g (H2SO4), 0.19g(underground soil) and 0.144g (fresh water) with corresponding corrosion rate 0.06725 (mm/yr.), 0.0177(mm/yr.), 0.002793(mm/yr.) and 0.001996 (mm/yr.) respectively. The follow up statistical analysis output showed that loss in weight is significant for tetraoxosulphate (VI) acid when compared with other media. Thus, it can be concluded that of the four media examined, tetraoxosulphate (VI) acid is the most corrosive, followed by hydrochloric acid, underground soil and fresh water which shows a fairly low degree of corrosiveness. Therefore, facilities and equipment made of mild steel should not be used in an environment containing traces of acidic ions due to the hazardous effect it has on mild steel material.
Keywords: mild steel; corrosion media; weight loss; corrosion rate; LAW/JURISPRUDENCE::Other law::Environmental law